The mechanical evaluation of cold asphalt emulsion mixtures using a new cementitious material comprising ground-granulated blast-furnace slag and a calcium carbide residue. (30th July 2020) - Dulaimi, Anmar; Shanbara, Hayder Kamil; Al-Rifaie, Ali
Highlights: CCR and GGBS were used as filler materials in cold asphalt emulsion mixtures (CAEMs). CCR improved the indirect stiffness modulus of the CAEMs. The impact of CCR-activated-GGBS on the performance of the CAEM's was examined. The microstructures of the BBF paste specimens were observed. Fatigue life and permanent deformation were investigated. Abstract: Cold asphalt emulsion mixtures (CAEMs) can be said to produce a reduced environmental impact and lower energy consumption in comparison to hot mix asphalt (HMA). They are also safer to use as there is no heating involved in the production and application of such mixtures. However, CAEMs are described as inferior to traditional HMA because of weak early strength and the length of curing time required to reach their full strength. As such, this piece of research aimed to develop new, CAEMs, a binary blended filler (BBF), made from ground-granulated blast-furnace slag (GGBS) and calcium carbide residue (CCR), as an alternative to traditional limestone filler (LF) in such mixtures. The new BBF mixture was compared to a mixture containing LF and with a control HMA. A significant improvement was reported in indirect tensile stiffness modulus (ITSM) when using CCR as the activator of GGBS. Early strength in terms of ITSM, was improved due to the activation of GGBS by the CCR. Scanning electron microscopy (SEM) analysis revealed that when added to GGBS, the CCR lead to considerable changes in the microstructure of components of the mix during the curing period. This confirmed the generation of the cementitious products ettringite, Portlandite and C-S-H gel. It is anticipated that the requirement for uninterrupted curing in the case of conventional CAEMs, will be eliminated through use of this new BBF mixture.